A novel junctional adhesion molecule A (CgJAM-A-L) from oyster (Crassostrea gigas) functions as pattern recognition receptor and opsonin. (February 2016) - Liu, Conghui; Wang, Mengqiang; Jiang, Shuai; Wang, Lingling; Chen, Hao; Liu, Zhaoqun; Qiu, Limei; Song, Linsheng
Abstract: Junctional adhesion molecule (JAM), a subfamily of immunoglobulin superfamily (IgSF) with a couple of immunoglobulin domains, can act as regulator in homeostasis and inflammation of vertebrates. In the present study, a structural homolog of JAM-A (designated CgJAM-A-L) was screened out from oyster, Crassostrea gigas, through a search of JAM-A D1 domain (N-terminal Ig domain in JAM-A). The cDNA of CgJAM-A-L was of 1188 bp encoding a predicted polypeptide of 395 amino acids. The immunoreactive area of CgJAM-A-L mainly distributed over the plasma membrane of hemocytes. After Vibro splendidus or tumor necrosis factor (CgTNF-1) stimulation, the mRNA transcripts of CgJAM-A-L in hemocytes increased significantly by 4.46-fold and 9.00-fold ( p  < 0.01) of those in control group, respectively. The recombinant CgJAM-A-L protein (rCgJAM-A-L) could bind multiple PAMPs including lipopolysaccharides (LPS), peptidoglycan (PGN), lipoteichoic acid (LTA), mannose (MAN), β-glucan (GLU) and poly(I:C), and various microorganisms including Micrococcus luteus, Staphylococcus aureus, Escherichia coli, Vibro anguillarum, V. splendidus, Pastoris pastoris and Yarrowia lipolytica . The phagocytic rates of oyster hemocytes towards Gram-negative bacteria V. anguillarum and yeast P. pastoris were significantly enhanced after the incubation of rCgJAM-A-L, and even increased more significantly after the pre-incubation of rCgJAM-A-L with microbes ( p  < 0.01). The results collectively indicated that CgJAM-A-L functioned as an important pattern recognition receptor (PRR) and opsonin in the immune defense against invading pathogen in oyster. Moreover, as the most primitive specie with homolog of JAMs, the information of CgJAM-A-L in oyster would provide useful clues for the evolutionary study of JAMs and immunoglobulins. Highlights: CgJAM-A-L, a homolog of JAMs, was identified from Crassostrea gigas . CgJAM-A-L mainly distributed over the plasma membrane of hemocytes. The expression of CgJAM-A-L was up-regulated by microbe and cytokine. CgJAM-A-L could bind PAMPs and microorganisms, and enhance phagocytosis.